The respiratory exercise significance in the olfaction restoration in the postcovid period - V. N. Nikolenko; M. V. Sankova; M. V. Zoller; M. V. Oganesyan; V. G. Zilov; D. A. Garkavy; A. E. Strizhkov (Спортивная медицина: наука и практика)
One of the pathognomonic COVID‑19 signs, occurring in 85‑98% of patients, is olfactory dysfunction, developing in the absence of pronounced inflammation and edema of the nasal mucosa. A promising medicine direction that helps restore microcirculation, increase blood oxygenation, improve metabolism and regenerate olfactory epithelial cells is the Nadi Shodhana breathing exercise technique.Objective: To assess the possibilities of using the pranayama technique as a method of restorative olfactory treatment in the post‑covid period.Materials and methods: 79 persons aged 22 to 68 years with olfactory disturbances occurring at COVID‑19 and persisting in the post‑covid period were examined. As a restorative treatment for olfactory disorders, the patients of the main group were offered a course of Nadi Shodhana breathing exercises, which is an alternate nostril breathing. Breathing training consisted of three such cycles performed three times a day at the same time for 15 days. The possibility of using the pranayama technique was assessed according to the visual analog scale. The control group consisted of 74 patients with olfactory disorders after COVID‑19 comparable in sex and age with the main group.Results: Olfactory disorders are characteristic of post‑COVID patients. Using Nadi Shodhana breathing exercise course can significantly reduce the olfactory dysfunction level in this patient category. It was showen that the pranayama technique is more effective in people under 40 years of age. It was also established that the olfaction restoration largely depends on the duration of the dysfunction period.Conclusion: The study results make it possible to recommend the using breathing exercises in patients underwent COVID‑19 to restore olfaction in the post‑COVID period.